27=2y-13

Simple and best practice solution for 27=2y-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27=2y-13 equation:


Simplifying
27 = 2y + -13

Reorder the terms:
27 = -13 + 2y

Solving
27 = -13 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
27 + -2y = -13 + 2y + -2y

Combine like terms: 2y + -2y = 0
27 + -2y = -13 + 0
27 + -2y = -13

Add '-27' to each side of the equation.
27 + -27 + -2y = -13 + -27

Combine like terms: 27 + -27 = 0
0 + -2y = -13 + -27
-2y = -13 + -27

Combine like terms: -13 + -27 = -40
-2y = -40

Divide each side by '-2'.
y = 20

Simplifying
y = 20

See similar equations:

| -(-9-6x-6y)= | | 980+n=1020 | | E=(8) | | -5=3x+8 | | -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 | | 5(3x-7)-(3x+9)= | | 19-u=238 | | -8(b-5)=-2(b+1) | | a-3[b-2(c-x)]=4 | | 167=2(3w-5)+2w | | 3x+6=9(x+4) | | 3(6p+5)=21 | | 3x+6=9(x+9) | | 7(4x+7)=6(1+x)-1 | | 2e^3x-2=7 | | C-13=5(3) | | 40=8(n-2) | | -5(8x+4)=-140 | | c=49.99-.25*49.99 | | 4[8-(-9x-1)]=180x+52 |

Equations solver categories